Resilient Cities urban nutrition profile: Sri Lanka - Margolies, Amy; Craig, Hope; Namara, Rebecca; Sehgal, Mrignyani; Hemachandra, Dilini; Olney, Deanna K. (International Food Policy Research Institute, 2024)
Key Messages Child stunting has declined in both rural and urban areas since 2016, but still affects a third of children on estates. Wasting prevalence has increased dramatically since 2016, reaching an alarming prevalence of 20 percent in urban areas. There is insufficient intake of nutritious foods, particularly in rural areas, and diet quality is negatively influenced by obesogenic food environments as the urbanization process continues. The cost of a healthy diet increased from $3.58 to $4.77 per person per day from 2017 to 2022, and 41 percent of the population is unable to afford a healthy diet. The prevalence of overweight, obesity and noncommunicable diseases is increasing nationally with higher burdens of overweight and obesity in urban populations and among women. National nutrition policies reference urban areas but do not adequately address the dual challenges of undernutrition (such as wasting) and overnutrition (such as overweight, obesity, and NCDs) common to urban contexts. Evidence is lacking on how to effectively address the double burden of malnutrition, yet clearly double-duty actions to address all forms of malnutrition will be essential.